2018
DOI: 10.1002/adom.201801239
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide‐Based Thermometers: At the Cutting‐Edge of Luminescence Thermometry

Abstract: Present technological demands in disparate areas, such as microfluidics and nanofluidics, microelectronics and nanoelectronics, photonics and biomedicine, among others, have reached to a development such that conventional contact thermal probes are not accomplished anymore to perform accurate measurements with submicrometric spatial resolution. The development of novel noncontact thermal probes is, then, mandatory, contributing to an expansionary epoch of luminescence thermometry. Luminescence thermometry base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
725
0
38

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 787 publications
(787 citation statements)
references
References 222 publications
(374 reference statements)
24
725
0
38
Order By: Relevance
“…In fact, they are even competitive with convential ratiometric thermometers (Sr ≥ 1 % · K -1 ) using two emission transitions from thermally coupled excited states. [88][89][90][91][92][93] In that sense, the presented compounds are also promising single-band luminescent thermometers.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, they are even competitive with convential ratiometric thermometers (Sr ≥ 1 % · K -1 ) using two emission transitions from thermally coupled excited states. [88][89][90][91][92][93] In that sense, the presented compounds are also promising single-band luminescent thermometers.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Tb-tfac outperformed the other complexes with am aximum sensitivity of 5.7 %K À1 at 300 K-amongst the highest valuesr eported for lanthanide complex-based luminescent thermometers. [56] Tb-acac was apt for al ower-temperature operation, whereas Tb-hfac showedamore limited usabilityd ue to the constraints imposed in terms of maximum operating temperature (i.e.,3 23 K) by the labile water molecule in the Tb 3 + coordinations phere.…”
Section: Spectroscopic Studies and Luminescence Thermometrymentioning
confidence: 99%
“…Based on this, they realized temperature measurement in a wide range of 100-700°C and achieved a high sensitivity of up to 4 × 10 −3 K −1 at 330 K. Moreover, since both excitation and emission wavelengths are located within the "optical window" of biological tissues, this luminescent nanothermometer may be used for biological temperature sensing. [111] Louika et al [112] reported a mixed Eu-Tb metal organic framework, [Tb 0.9 Eu 0.1 (1,3-bdc) 3 (H 2 O) 2 ]·H 2 O, as a luminescent thermometer, in which the luminescence intensity ratio of Tb 3+ to Eu 3+ presented the classical Mott-Seitz model temperature dependence in the 12-230 K range. [60] Lanthanide organic frameworks have also been investigated as a fascinating class of luminescent thermometers with excellent performance in the past few years.…”
Section: Temperature Sensingmentioning
confidence: 99%